Non-isothermal (trans)esterification of linoleic acid and soybean oil deodorizer distillate with methanol under subcritical conditions. (September 2022) - Xiong, Yi-Wei; Go, Alchris Woo; Alivio, Roxanne Kathlyn O.; Santoso, Shella Permatasari; Angkawijaya, Artik Elisa; Soetaredjo, Felycia Edi; Agapay, Ramelito C.
Abstract: Soybean oil deodorizer distillates (SODD), a by-product of soybean oil refining, primarily comprised of free fatty acids (FFA, 40.62–51.23 wt%), acyglycerides (22–25 wt%), and unsaponifiable matter (19.81–42.23 wt%), was explored as a potential feedstock for the synthesis of fatty acid methyl ester under subcritical conditions. Oil mixtures of linoleic acid and soybean oil were used as models to investigate the effects of reactor loading (RL = 25, 50, 90%), solvent-to-fatty acid ratio (SFR = 0.15–1.5 mL/g), mixing (0, 300 rpm), temperature (30–245 °C), and reaction time under non-isothermal and isothermal conditions. In addition, water and acetic acid were used as additives to investigate their effect on the reaction. Under favorable reaction conditions of 90% RL, SFR of 0.5 mL/g, and reacted non-isothermally to 245 °C and held for 100 min with stirring, high conversions or yields (87–89%) could be achieved when using SODDs having different total fatty acid content (59.37–77.42 wt%). The effect of unsaponifiable matter in significant quantities and some simple strategies to overcome possible limitations in the use of such feedstock were also looked into. The presence of high FFA allows (trans)esterification to be carried out under subcritical conditions without the need of adding a catalyst. Graphical abstract: Image 1